Phrenic nerve block during nonintubated video-assisted thoracoscopic surgery: a single-centre, double-blind, randomized controlled trial - Yi Zhu (Nature Portfolio, 2021)
Abstract There has been interest in the use of nonintubated techniques for video-assisted thoracoscopic surgery (VATS) in both awake and sedated patients. The authors’ centre developed a nonintubated technique with spontaneous ventilation for use in a patient under general anaesthesia using a phrenic nerve block. This treatment was compared with a case-matched control group. The authors believe that this technique is beneficial for optimizing anaesthesia for patients undergoing VATS. The patients were randomly allocated (1:1) to the phrenic nerve block (PNB) group and the control group. Both groups of patients received a laryngeal mask airway (LMA) that was inserted after anaesthetic induction, which permitted spontaneous ventilation and local anaesthesia in the forms of a paravertebral nerve block, a PNB and a vagal nerve block. However, the patients in the PNB group underwent procedures with 2% lidocaine, whereas saline was used in the control group. The primary outcome included the propofol doses. Secondary outcomes included the number of propofol boluses, systolic blood pressure (SBP), pH values of arterial blood gas and lactate (LAC), length of LMA pulled out, length of hospital stay (length of time from the operation to the time of discharge) and complications after 1 month. Intraoperatively, there were increases in lactate (F = 12.31, P = 0.001) in the PNB group. There was less propofol (49.20 ± 8.73 vs. 57.20 ± 4.12, P = 0.000), fewer propofol boluses (P = 0.002), a lower pH of arterial blood gas (F = 7.98, P = 0.006) and shorter hospital stays (4.10 ± 1.39 vs. 5.40 ± 1.22, P = 0.000) in the PNB group. There were no statistically significant differences in the length of the LMA pulled out, SBP or complications after 1 month between the groups. PNB optimizes the anaesthesia of nonintubated VATS.